Temperature memory effect in shape memory materials for overcooling monitoring - Bai, Jing (2016)
Nowadays, Shape Memory Effect (SME) in Shape Memory Materials (SMMs) has been well researched and applied in many fields, such as sensor, actuator, biomedical device and so on. Recently, Temperature Memory Effect (TME) has been found in many SMMs and extensive researches have been carried out to TME in Shape Memory Alloy (SMA). However, there have been only a few researches focusing on TME in Shape Memory Polymers (SMPs) and even less in Shape Memory Composites (SMCs). One of such researches focusing on TME in SMP is Mr Leow Wei Chong Engene’s final year project conducted last year, which was named temperature memory effect in shape memory polymer for overheating monitoring. His report shows TME in overheating process for TPU-265A has been well studied in his project and TPU-265A could be a suitable material for heating sensor if the operation temperature is within the range of 40 ℃ to 54 ℃. Overcooling test was also conducted by him for the same material. However, no obvious kinetic stop appeared either in the current overcooling cycle or the next full cycle. And thus no conclusion was drawn for overcooling monitoring in his report. In the present final year project, the author targeted to use enthalpy of the subsequent melting process, instead of kinetic stop, to memorize the stopping temperature in the overcooling process and thus overcooling monitoring can be achieved. During the project, a series of DSC tests were conducted to collect the raw data and TA Universal Analysis and Origin software were used to analyze the raw data. As a result, relation between stopping temperature in overcooling process and enthalpy in the subsequent melting process was established for both TPU-265A and Melting Glue (MG). Most importantly, the relation built for melting glue, which was generated by conducting a series of DSC tests and analyzing abundant raw data, can be simulated using an analytical result by conducting two-cycle DSC test and the simulation result is quite accurate with a deviation of 0.5 ℃. The results achieved in this project take a step forward in the journey of exploring TME in SMP and SMC for overcooling monitoring. Although some findings in this project may not be very useful right now, the research approaches can be used to explore TME in other materials. Lastly, melting glue was found out might not suitable to be used as cooling sensor. However, it is a very promising material for heating sensor with an accuracy of ±0.2 ℃.